2021
DOI: 10.1021/acs.est.1c06747
|View full text |Cite
|
Sign up to set email alerts
|

Freeze–Thaw Cycle-Enhanced Transformation of Iodide to Organoiodine Compounds in the Presence of Natural Organic Matter and Fe(III)

Abstract: The formation of organoiodine compounds (OICs) is of great interest in the natural iodine cycle as well as water treatment processes. Herein, we report a pathway of OIC formation that reactive iodine (RI) and OICs are produced from iodide oxidation in the presence of Fe­(III) and natural organic matter (NOM) in frozen solution, whereas their production is insignificant in aqueous solution. Moreover, thawing the frozen solution induces the further production of OICs. A total of 352 OICs are detected by Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 93 publications
1
19
0
Order By: Relevance
“…Various iodine compounds (e.g., IO, I 2 , HOI, ICl, OICs) are found in the sea ice of Antarctic and the atmosphere of polar boundary layers. ,, The enhanced concentrations of iodocarbons were often observed in sea ice samples relative to the sea water below. ,, The emission of RI and volatile OICs from sea ice to the atmosphere via the brine channels of ice may arouse iodine cycling in and over sea ice . Although biotic processes have been proven to produce iodocarbons or RI in sea ice, , abiotic oxidation of iodide in ice has also been proposed as an alternative source in frozen environments. ,, Our previous studies revealed abiotic transformation pathways of iodide by Fe­(III)/iron oxides in frozen or freeze–thaw cycled solutions. , However, the effective oxidation of iodide in frozen iron­(III) systems requires an acidic condition (pH < 5.0), which limits the formation potential of OICs in natural environments. In this study, three ubiquitous forms of manganese dioxides were selected to investigate the oxidation of iodide in frozen media.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various iodine compounds (e.g., IO, I 2 , HOI, ICl, OICs) are found in the sea ice of Antarctic and the atmosphere of polar boundary layers. ,, The enhanced concentrations of iodocarbons were often observed in sea ice samples relative to the sea water below. ,, The emission of RI and volatile OICs from sea ice to the atmosphere via the brine channels of ice may arouse iodine cycling in and over sea ice . Although biotic processes have been proven to produce iodocarbons or RI in sea ice, , abiotic oxidation of iodide in ice has also been proposed as an alternative source in frozen environments. ,, Our previous studies revealed abiotic transformation pathways of iodide by Fe­(III)/iron oxides in frozen or freeze–thaw cycled solutions. , However, the effective oxidation of iodide in frozen iron­(III) systems requires an acidic condition (pH < 5.0), which limits the formation potential of OICs in natural environments. In this study, three ubiquitous forms of manganese dioxides were selected to investigate the oxidation of iodide in frozen media.…”
Section: Resultsmentioning
confidence: 99%
“…For samples containing FA, dissolved OICs were calculated from the difference between total dissolved iodine and total dissolved inorganic iodine (the sum of iodide, RI, and iodate) in the filtered sample. Total dissolved iodine was analyzed by the heating-activated persulfate oxidation method according to the previous study. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the P i,n of region III (regarded as fulvic acid-like compounds) and region V (regarded as humic acid-like substances) declined from 7.96% to 17.31% in the control to 5.05% and 10.87%, respectively with the addition of 100 mg PI per g TS. The potential reason for this decrease might be due to the powerful oxidative activity of PI (E 0 = +1.60 V vs. standard hydrogen electrode (SHE)) [ 37 ], which could destroy carbon double bonds and benzene rings and thereby benefit the degradation of recalcitrant organics [ 5 ]. On the other hand, the production of strong oxidizing radicals in PI-pretreatment systems, i.e., •OH, •O 2 − , and 1 O 2 , might promote the conversion of refractory substances.…”
Section: Resultsmentioning
confidence: 99%
“…The production of I 2 in the presence of I – and O 2 was considerably enhanced when the aqueous solution was frozen under both dark and light-irradiation conditions . Freezing accelerated the production of I 2 via the chemical reaction of I – with iron oxides, chromate, or ferric ions. Although the production of I 2 via NO 2 – -mediated oxidation of I – was negligible in water, it was clearly observed in ice. The freeze concentration effect is considered to be the main reason for the noteworthy enhanced production of I 2 from I – in ice. At temperatures between the freezing and eutectic points, frozen solutions contain both solid and liquid phases, which are referred to as bulk ice crystals and ice grain boundaries, respectively .…”
Section: Introductionmentioning
confidence: 99%